2013
DOI: 10.1097/scs.0b013e31828026d8
|View full text |Cite
|
Sign up to set email alerts
|

Facial Lacerations in Children

Abstract: The aim of this study was to evaluate the demographics and treatment of facial lacerations in pediatric patients. A retrospective record-based analysis was administered on 3783 patients (<15 years of age) presenting with facial lacerations from March 2002 to February 2011. Males were injured more frequently across all age groups (65.3%) and especially in the 13- to 15-year-old group (81.3%) (P = 0.012, Pearson χ). Overall, 48.9% of injuries occurred outdoors and 45.1% in homes. Only 6.0% occurred in schools or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
6
6
1
Order By: Relevance
“…The percentages of males and females with a facial laceration that underwent primary repair in the emergency room between March 2011 and February 2013 were 72.6% (2,348) and 27.4% (886), respectively. The M/F ratio for all study subjects was 2.65, and the bias toward men was greatest in adolescents, as has been mentioned previously in several reports [ 3 , 4 , 5 , 6 ]. In adolescents, the proportion of males was significantly higher than in the other groups (P<0.001).…”
Section: Discussionsupporting
confidence: 80%
“…The percentages of males and females with a facial laceration that underwent primary repair in the emergency room between March 2011 and February 2013 were 72.6% (2,348) and 27.4% (886), respectively. The M/F ratio for all study subjects was 2.65, and the bias toward men was greatest in adolescents, as has been mentioned previously in several reports [ 3 , 4 , 5 , 6 ]. In adolescents, the proportion of males was significantly higher than in the other groups (P<0.001).…”
Section: Discussionsupporting
confidence: 80%
“…Results of this study revealed that facial lacerations were predominantly distributed around the midline region of the face following a T-shaped distribution, over the forehead, upper orbit, upper lip, lower lip and chin. Similar findings have been reported in other literature (Lo and Aslam, 2005;Roccia et al, 2011;Hwang et al, 2013). The prevalence of lacerations with a T-shaped distribution is attributed to the anatomic bony prominences of the maxillofacial region, which predisposes an individual to soft tissue injuries (Roccia et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…This could highlight the role of teachers and parents in injury prevention, in particular to ensure there is adequate supervision and to provide a safe environment for the children. Injuries occurred least frequently between midnight and 6 AM, because children are sleeping, which is supported by the conclusion of Kun Hwang et al 11 The monthly distribution peaked in December (1222, 11.25%) and revealed the lowest occurrence in June (770, 7.09%). We speculated that the higher number of injuries in December may be relevant with the wearing of clothes and shoes.…”
Section: Disscusionsupporting
confidence: 59%
“…It is thought that children move to protect their forehead as age increases. 11 In the study, bumping, including hitting the ground, wall, stair, furniture, and so forth after tumbling or slipping, was the most frequent cause of injury in preschool-aged children, with higher prevalence among the younger age groups. Several factors contribute to these findings: (a) with increasing age, security of motion and balance increases.…”
Section: Disscusionmentioning
confidence: 93%